Cours de phonetigue Francais = French phonetics [soundrecording] - Dastugue, Jean; Brown, Bill (Intellectual Publishing, 1987)
French is a language which as an alphabetic system of writing and the letter is the smallest unit in orthography. The French alpbabet consists of 26 letters: 6 vowels and 20 consonants. Each letter has its name. The sounds of French are represented by 36 speech sounds, 16 vowels and 20 consonants.